„Женщины в темноте". Świadectwa wojny w twórczości Iriny Sieriebriakowej - Charko-Klekot, Paulina (Studia Rossica Posnaniensia, 2025)
This article aims to explore the traces of anti-war discourse in the work of Irina Serebryakova, a Ukrainian playwright, screenwriter and interpreter. Following Russia's attack on Ukraine in February 2022, the author turned her work towards capturing the changes that war forces on the lives of ordinary people. Serebryakova's dramas record the forced reorganisation of various planes of everyday existence: professional, living or emotional. She presents the relationship between man and war from different perspectives, e.g. in the piece In the Instagram, we will live forever she tackles the problem of looters stealing from flats during bombing raids, but also refugees from the Warsaw train station. The text Women in the dark, written with Masha Denisova, is, in turn, a kind of diary from Russian-besieged Kyiv, written using the verbatim technique. Apart from that, in the play My best Iranian friend, the author combines the traumas of war with the issue of intolerance and national-religious discrimination.